OBLITERATIVE VASCULAR DISEASES, OBLITERATIVE ENDARTERITIS, AND MODERN TREATMENT METHODS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The latest achievements and innovative approaches in the field of medicine have significantly expanded the possibilities for effective treatment of these diseases. Types of obliterative vascular diseases, causes, diagnostic methods, and the most modern treatment methods.